Distribution of the content of new media: trends and specificity - Zaitsau, Maksim L. (Journal of the Belarusian State University. Journalism, 2019)
The mass media’s approaches to work with content distribution undergo a significant change due to technological processes and evolution in users’ interpersonal communication. This leads to the experimental practice of mass media work in that field. The major trends in the broadcast of content by world’s and Belarusian media companies, the new concepts of interaction with the audience are considered in the article, as well as the transformations of content in terms of subject and form are analyzed.